Fertilizer and conflicts: Evidence from Myanmar - Takeshima, Hiroyuki; Minten, Bart; van Asselt, Joanna; Lambrecht, Isabel B.; Masias, Ian; Goeb, Joseph; Aung, Zin Wai; Htar, May Thet (Elsevier, 2025)
The number of farmers residing in fragile and conflict-affected countries is rising globally, yet the impacts of conflict on the economics of inorganic fertilizer in these settings remain poorly understood. We study how conflicts in Myanmar, combined with global fertilizer market disruptions, have affected inorganic fertilizer prices, use, response, and efficiency. We utilize unique nationally representative household panel survey data and a comprehensive approach that employs various analytical methods to examine the nexus between conflicts and fertilizer-related issues. Our findings reveal that greater intensity of violent events is associated with higher prices of major types of inorganic fertilizer, particularly in areas farther from major import locations. These price changes and increases in violent events have suppressed both the likelihood and quantity of inorganic fertilizer usage, leading to decreased rice yield responses at given nitrogen application levels. Panel stochastic frontier analyses, combined with a method addressing the endogeneity of inorganic fertilizer use, suggest a significant decline in fertilizer use efficiency each year since the onset of conflict. The increase in violent events is also associated with the reduced use of extension services, seeds from markets, irrigation, and optimal fertilizer blends, which may partly explain the diminished returns and efficiency of inorganic fertilizer use. Conflict therefore seems to be associated with a change in the economics of inorganic fertilizer use through various impact channels, affecting agricultural performance in these fragile and conflict-affected settings.